Bilateral lower limb gangrene due to HIV vasculitis – a rare case - D. Majumdar; S. Chakraborty; S. Pandey; S. Bhattacharya; B. Bhattacharjee; A. Naskar; B. Saha (Sri Lankan Journal of Infectious Diseases, 2017)
Human immunodeficiency virus (HIV) positive patients may develop vasculitis, either mediated by immunological factors or by direct vascular injury. It may also be caused by infectious agents or by some nonspecific causes. We describe a patient who developed manifestations suggestive of extremities vasculitis (occlusive variety) with no identifiable risk factors other than HIV. He responded to steroid and combination anti-retroviral therapy